Who may benefit from lower dosages of intravenous tissue plasminogen activator? Results from a cluster data analysis. Issue 4 (1st July 2020) - Dong, Yi; Han, Ye; Shen, Haipeng; Wang, Yilong; Ma, Frank; Li, Hao; Wang, Yongjun; Dong, Qiang
Abstract : Background: The risk of symptomatic intracranial haemorrhage (sICH) after thrombolysis is low but severe. Lower dose of alteplase may reduce the risk of sICH. We aim to identify subsets of patients who could beneﬁt from lower dose of alteplase compared with standard dose. Methods: Data from two observational registries were pooled together. A total of 3479 patients who had acute ischaemic stroke were entered into the interaction tree model. The response variable was the rate of sICH per the definition of the National Institute of Neurological Disorders and Stroke Study. Clinical improvement was measured by the National Institutes of Health Stroke Scale (NIHSS) and defined as NIHSS 0 or 1 or an improvement of more than 4 points (within 7 days or at discharge). Rare event logistic regression was performed to analyse the OR of safety outcome. Results: To optimise the interaction effect between tissue plasminogen activator (tPA) dosage (standard/lower) and patient subgroups, three subgroups based on the severity of stroke were identified: (1) NIHSS ≤4, (2) NIHSS between 5 and 14, and (3) NIHSS ≥15. The estimated difference of OR of having sICH was 2.71 (95% CI 0.80 to 7.69, p=0.10) for mild, 0.13 (95% CI 0.02 to 0.68, p=0.01) for moderate, and 0.65 (95% CI 0.19 to 2.55, p=0.52) for severe, respectively. In addition, patients who had moderate stroke treated with lower dose had comparable efficacy outcome (OR 1.23, 95% CI 0.71 to 2.13, p=0.45). Conclusion: Our analysis demonstrated that in patients who had moderate stroke, lower doses of alteplase are associated with significant sICH reduction and non-inferior performance in efficacy, compared with those in the standard dose group. Trial registration number: The TIMS-China was a national prospective stroke registry on thrombolytic therapy using intravenous tPA in patients who had acute ischaemic stroke. The results were initially published in 2012 without a clinical trial registration number. The Shanghai Stroke Service System was registered at www.clinicaltrial.gov (NCT02735226 ).